Sustainable Management of Catchment areas of the Koto Panjang Hydroelectric Reservoir - Rahmat, Aan Nur; Mubarak, Mubarak; Putra, Ridwan Manda (Faculty of Fisheries and Marine, Universitas Riau, 2020)
Riau Province has many lakes and reservoirs, one of which is the Koto Panjang Hydroelectric Reservoir, Sustainability of the Koto Panjang Hydroelectric Reservoir Unstable water continuity, drought during the dry season and flooding during the rainy season have caused this power plant to be not optimal, one of the ways that can done to overcome complications in certain areas. Koto Panjang Hydroelectric Reservoir Water is that by using the analysis of the Koto Panjang Hydroelectric Reservoir we can arrange steps in managing the maintenance of the Koto Panjang Hydroelectric Reservoir. Sustainability analysis conducted using the RAP-catchment area application on three dimensions, namely ecology, economics and social, the results of the analysis that have been carried out on the ecological dimension address an index of 52.31 which is classified as quite sustainable in the social dimension category 41.98 which is classified as less sustainable. To improve the index of sustainability in the management of water areas, several management directives are needed, namely reforestation or greening of open land related to rivers and conducting training in environmentally friendly agriculture to provide and support the protection of farming communities and communitiesrelated to fire, develop the potential of natural resources such as tourist attractions as alternative livelihoods to increase community income and increase socialization and encourage people in need in hydropower reservoir catchment areas.